Mental Health: Menyikapi Fenomena Bunuh Diri Perspektif Ajaran Agama Hindu (Pramana: Jurnal Hasil Penelitian, 2024)
The phenomenon of suicide is a complex and deep mental health issue, requiring a holistic and sensitive approach. In the context of Hinduism, views on suicide are influenced by spiritual and philosophical principles that shape understandings of life and death. This material aims to explore how Hindu religious teachings address suicide, focusing on key concepts such as karma, reincarnation, ahimsa (non-violence), and dharma (moral obligation). In Hinduism, suicide is seen as an act that has serious karmic implications and can hinder the soul's spiritual journey towards moksha (liberation). Hindu teachings emphasize the importance of practicing dharma and overcoming life's challenges as part of the spiritual journey. Therefore, suicide is considered to be contrary to an individual's spiritual goals and moral responsibilities. This material will discuss how Hindu values ​​influence views on suicide, as well as how the Hindu community can approach mental health issues with more empathy and support. By integrating a spiritual perspective in understanding suicide, it is hoped that it can provide deeper insight and support the creation of an environment that is more sensitive to mental health. Through this analysis, it is hoped that readers will develop a better understanding of the ways Hinduism can play a role in preventing suicide and providing support for individuals struggling with mental health issues, as well as promoting more inclusive and supportive dialogue in spiritual and cultural contexts.
Keywords: Mental Health; Suicide; Hinduism